A porous bone fixation material having osteoinductive function

CN122849556BActive Publication Date: 2026-11-03SHANDONG BRANDEN MEDICAL DEVICE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611355072.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-09-03
Publication Date
2026-11-03
Estimated Expiration
2046-09-03

AI Technical Summary

Technical Problem

现有骨固定材料存在应力遮挡、界面结合差、远期松动、无骨诱导及愈合难以监测的问题,同时X射线照射对骨细胞造成损伤。

Method used

A porous bone fixation material is used, comprising modified low-modulus polymethyl methacrylate (PMMA), calcium phosphate, magnesium phosphate or calcium sulfate bone cement as the matrix, with the addition of anchoring factors, repair factors and protective factors. A porous structure is formed by a porogen, combined with a contrast agent, to match the mechanical parameters of the host bone and protect bone cells during X-ray irradiation.

Benefits of technology

It achieves mechanical adaptation between the material and the host bone, promotes osteocyte anchoring and repair, reduces X-ray damage, and can monitor healing progress through X-rays, thus avoiding stress-shielded osteoporosis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122849556B_ABST
    Figure CN122849556B_ABST
Patent Text Reader

Abstract

The application discloses a porous bone fixation material with bone inductive function, and belongs to the field of medical devices. The material base constructs a porous structure matching the size of bone cells; the inner surface of the pores is biologically modified to construct a microenvironment conducive to the adhesion and creeping growth of bone cells; the composition of the porogen is customized according to the mechanical requirements of the fracture site to precisely control the in-vivo degradation period. The porogen is foamed or degraded to form a porous structure on the bone fixation material for the growth of new bone. The system is combined with a medical developing component, and the bone healing process can be monitored through X-ray. The application can effectively reduce the mechanical and physicochemical performance difference between the implanted material and the natural bone, eliminate the stress shielding effect, realize the integration of the implant and the host bone, significantly reduce the long-term loosening and secondary fracture risk, and is suitable for vertebral compression fracture, limb bone trauma and bone defect repair surgery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of medical devices, specifically relating to a porous bone fixation material with bone-inducing function. Background Technology

[0002] Bone cement infusion is a widely used treatment for bone trauma and vertebral compression fractures. However, the currently mainstream polymethyl methacrylate (PMMA) bone cement has significant technical drawbacks: (1) The elastic modulus of the material is much higher than that of human cortical bone and cancellous bone, and stress shielding effect is generated after implantation; the load is mainly borne by bone cement, and the surrounding host bone lacks mechanical stimulation for a long time, gradually developing stress shielding osteoporosis.

[0003] (2) Bone cement and bone tissue are only mechanically interlocked, without bone tissue ingrowth and no biological bonding; in the long term, interface micromovement, fixation loosening, and bone cement displacement may occur, which may induce adjacent vertebral fractures in severe cases, requiring revision surgery.

[0004] (3) Traditional dense bone cement has no biological activity, no bone induction ability, and cannot promote bone regeneration.

[0005] (4) Lack of postoperative imaging observation means it is difficult to intuitively assess the bone healing status of the bone cement-bone interface.

[0006] Therefore, developing a bone fixation material that can solve the above problems is of great practical significance.

[0007] In recent years, people have carried out many meaningful explorations in the development of bone fixation materials.

[0008] Patent 2026101979055 discloses a porous bone cement, which is composed of three components: bone cement powder, liquid A, and liquid B. By simultaneously generating gas and creating pores through magnesium powder and water in liquid B, a porous structure with interconnected internal structures is formed. This reduces the elastic modulus to avoid stress shielding while ensuring the mechanical requirement of compressive strength ≥70MPa. Liquid B can integrate antibacterial and bone integration promotion functions, and the contrast agent is suitable for postoperative monitoring.

[0009] Patent 2025120218445 discloses a multi-layer biodegradable porous bone scaffold for bone repair. The porous bone scaffold, through its multi-layer gradient structure design, can simulate the gradient pore structure of human bones, achieve a high degree of fit with the real human bone structure, improve bone ingrowth efficiency, enhance bone repair effect, and at the same time have good mechanical support performance and controllable degradation performance.

[0010] Patent 2026105833226 provides a silicon nitride ceramic slurry for biomimetic porous bone implants. The slurry utilizes the slow decomposition of diamine hydrogen citrate in its components at low temperatures to generate gas and form micropores, while polystyrene microspheres decompose at high temperatures to generate macropores. The macropores construct biomimetic channels for bone ingrowth, while the micropores are diffusely distributed within the pore walls to passivate stress, prevent crack propagation, and absorb deformation energy. The two work synergistically to achieve high porosity and high flexural strength.

[0011] Patent 2026105933402 discloses an antibacterial intramedullary nail for ankle fusion. The main body of the intramedullary nail is a fully porous structure or a hybrid structure of porous and solid structures. Zinc, copper, and silver ions in the in-situ growth membrane layer of the intramedullary nail have broad-spectrum antibacterial effects, calcium and phosphorus functional substances can induce the formation of hydroxyapatite, and the porous structure provides anchoring points for bone ingrowth, promoting the bony fusion of the intramedullary nail with the host bone.

[0012] Patent 2026105933436 discloses an ankle joint talus prosthesis with an antibacterial porous interface. The prosthesis achieves the dual functions of promoting osteointegration and preventing infection by constructing an antibacterial bioactive composite coating at the porous osteointegration interface.

[0013] Patent 2026109337371 discloses a porous magnesium alloy bone nail that promotes bone regeneration. The second bioactive layer of the bone nail is a strontium and zinc co-doped nano-hydroxyapatite layer, which can simultaneously achieve the dual biological functions of inducing osteoblast proliferation and differentiation and long-lasting antibacterial and anti-inflammatory effects. The third sustained-release layer adopts a PLLA / PLGA / chitosan ternary cross-linked interpenetrating polymer porous sustained-release layer. Through phase separation pore-forming technology, an ion-responsive porous network is formed, which simultaneously loads four types of active substances: VEGF, BMP-2, zinc ion microparticles, and strontium ion microparticles. It distinguishes between the three stages of early vascularization, mid-term bone induction, and late-stage bone remodeling, and matches the corresponding release kinetic model to achieve gradient time-sequential release of active substances, which conforms to the physiological needs of the entire bone repair cycle.

[0014] However, the inventions mentioned above still fail to fully realize the effect of constructing a microporous microenvironment to promote osteoblast anchoring, migration and self-repair, and at the same time cannot effectively protect against and repair damage caused by X-ray irradiation. Summary of the Invention

[0015] This invention aims to overcome the shortcomings of existing technologies, such as stress shielding, poor interfacial bonding, long-term loosening, lack of bone induction, and difficulty in monitoring healing. Even though X-rays can detect bone healing, the radiation from X-rays also damages bone cell growth. This invention provides a porous bone fixation material with bone induction function, which achieves mechanical adaptation and biological bone integration between the implant material and the host bone tissue, eliminates stress shielding osteoporosis, and protects against X-ray damage while allowing bone healing to be detected. To achieve the above objectives, the technical solution adopted by the present invention is as follows: A porous bone fixation material with bone-inducing function, comprising a matrix, a porogen, and a contrast agent.

[0016] The porous bone cement matrix is ​​selected from modified low-modulus polymethyl methacrylate (PMMA) bone cement, calcium phosphate bone cement, magnesium phosphate bone cement, or calcium sulfate bone cement.

[0017] The matrix contains anchoring factors, repair factors, and protective factors. Anchoring factors promote osteoblast anchoring, repair factors promote osteoblast repair, and protective factors reduce damage caused by X-ray irradiation and repair X-ray irradiation damage in subsequent processes. During the use of porous bone fixation materials, anchoring factors, repair factors, and protective factors are slowly released, promoting osteoblast anchoring within the porous bone fixation material, promoting the repair of osteoblasts around the porous bone fixation material, protecting osteoblasts, reducing damage caused by X-ray irradiation, and repairing X-ray irradiation damage in subsequent processes.

[0018] Furthermore, the overall degradation cycle of the biodegradable matrix material is matched with the degradation cycle of the porogen. After the porogen is completely degraded to form a through-porous structure, the matrix can still maintain mechanical support. It gradually degrades after the bone tissue is fully integrated, thus achieving a match between mechanical support and bone regeneration time.

[0019] Furthermore, the anchoring factor promotes osteocyte anchoring, and the anchoring factor is one or more combinations of GFOGER peptide, type I collagen P15 peptide, and fibronectin VN fragment; the repair factor is one or more combinations of recombinant bone morphogenetic protein-2 (BMP-2), teriparatide PTH (1-34), and strontium ion (Sr²⁺); the protective factor is one or more combinations of magnesium ion, selenium ion, strontium ion, zinc ion, cerium oxide nanozyme, amifostine, N-acetylcysteine, SOD mimic peptide, resveratrol, or miR-34a.

[0020] The porogen is distributed within the matrix. There is no single porogen; they are categorized into foaming porogens and biodegradable porogens. Through foaming or degradation, a porous structure is formed on the bone fixation material, facilitating the ingrowth of new bone. The pore size of the porous structure matches the size of bone cells, ranging from 200-800 μm. This porous structure reduces stress in the porous bone fixation material, regulating the elastic modulus to 0.5-18 GPa, matching the mechanical parameters of human cancellous and cortical bone. The cancellous bone implantation area utilizes a large pore size of 500-800 μm, while the cortical bone implantation area uses a small pore size of 200-500 μm. This gradient porous structure further matches the elastic modulus of the host bone, completely avoiding stress concentration and stress shielding issues, and improving bone integration efficiency.

[0021] Foaming and pore-forming agents rely on chemical reactions to release carbon dioxide / oxygen, generating bubbles during the curing stage of the paste. The foaming agent system is one of the following: sodium bicarbonate-citric acid system, carbonate system, ammonium bicarbonate / ammonium carbonate system, or hydrogen peroxide system.

[0022] Biodegradable porogens are selected based on the implantation site, with varying types, degrees of cross-linking, and particle sizes to achieve controllable in vivo degradation cycles. The biodegradable porogen constitutes 8%-25% of the matrix by mass, and the doping ratio can be matched to the required porosity and bone regeneration rate, ensuring a stable porosity of 30%-65% in the porous structure, balancing overall material mechanical strength with space for bone cell ingrowth. Biodegradable porogens are selected from microspheres and microcapsules made of gelatin, chitosan, PLGA, and alginate, with particle sizes ranging from 200-800 μm, consistent with the pore size of the porous structure. The in vivo degradation cycle of the biodegradable porogen can be controlled within a range of 3-24 months, adapting to the bone healing cycle.

[0023] The bio-activated modified layer on the inner surface of the porous structure is formed by the residual capsule wall after the microcapsule wall in the porogen degrades and ruptures. The thickness is 1-5 μm. The microcapsule wall contains anchoring factors and protective factors. In addition to protective factors, the inner cavity of the microcapsule also contains migration factors. The migration factors have the effect of inducing osteoblast migration. The modified layer uniformly covers the inner surface of the porous structure, does not block the pores or change the original pore size structure, stably carries the active factors and continuously exerts the effects of osteoinduction and anti-radiation damage. Specifically, the degradation rate is faster at the contact points between the capsule wall and the external tissue fluid than at other locations. The microcapsules rupture, and the migration and protective factors within are rapidly released, forming a cavity where the remaining capsule wall adheres to the bone cement. This creates a microenvironment for anchoring osteocytes and inducing their migration or repair. The released migration factors promote osteocyte growth, causing them to embed themselves into the ruptured microcapsules. The capsule wall releases anchoring factors, promoting cell anchoring to the capsule wall. After the capsule wall degrades, these cells further anchor and fill the porous structure of the bone cement, promoting the fixation and fusion of autologous osteocytes and bone cement. The protective factors released from the capsule wall protect osteocytes during their growth and anchoring process, reducing damage caused by X-ray irradiation.

[0024] Furthermore, the migration factor is one or a combination of several of SDF-1α (CXCL12), E7 (SDF-1α mimic peptide), and PDGF-BB.

[0025] The proportion of microcapsules in the pore-forming agent is 10%-50% of the proportion of microspheres, meaning that 2-10 microspheres surround each microcapsule. The microspheres are solid, and their degradation rate is faster at the contact sites with external tissue fluid than at other locations. As the microspheres degrade, they release repair, protective, and migration factors, achieving a sustained-release effect. This continuously promotes the growth of osteocytes within the capsule wall and reduces and repairs radiation-induced damage during X-ray irradiation. The microcapsules and microspheres synergistically promote osteocyte growth and anchorage.

[0026] Furthermore, the contrast agent is uniformly dispersed in the matrix, and the bone healing can be monitored by X-rays; the contrast active component is selected from one or more combinations of barium sulfate, strontium-doped hydroxyapatite, and tantalum particles, with an added mass fraction of 2%-12%.

[0027] Compared with the prior art, the present invention has the following key beneficial effects: (1) By adjusting the elastic modulus of the material to 0.5-18GPa through the porous structure, the mechanical parameters of human cancellous bone and cortical bone are matched, thus fundamentally eliminating stress shielding osteoporosis.

[0028] (2) The cancellous bone implantation area uses a large pore size of 500-800μm, and the cortical bone implantation area uses a small pore size of 200-500μm, to further match the elastic modulus of the host bone and completely avoid stress concentration and stress shielding problems.

[0029] (3) The porosity is stable at 30%-65%, which not only ensures the overall mechanical strength of the material, but also provides sufficient space for bone cells to grow in.

[0030] (4) A 1-5 μm bio-activated modified layer is provided on the inner surface of the porous structure to uniformly cover and not block the pores, thereby creating a microenvironment for anchoring osteocytes and inducing osteocyte crawling and repair.

[0031] (5) Anchoring factors promote osteoblast anchoring; repair factors promote osteoblast repair and growth; migration factors promote osteoblast migration and ingrowth into porous structures.

[0032] (6) The microcapsule wall ruptures first to rapidly release migration and protective factors, and the remaining capsule wall serves as an anchoring scaffold; the surrounding 2-10 solid microspheres slowly degrade to release repair, protective and migration factors, achieving long-term sustained release. The two work together to promote bone cell growth and anchoring, and finally fill the porous structure to achieve fixation and fusion of autologous bone and implanted material.

[0033] (7) The contrast agent is uniformly dispersed in the matrix, and the progress of bone healing can be clearly monitored by X-ray.

[0034] (8) Protective factors reduce X-ray damage during bone cell growth and anchoring, and subsequently repair radiation damage, thus achieving a balance between "detectability" and "damage prevention".

[0035] (9) The type, degree of cross-linking and particle size of the pore-forming agent can be selected according to the implantation site. The in vivo degradation cycle can be controlled within the range of 3-24 months to accurately match the bone healing cycle.

[0036] (10) The overall degradation cycle of the biodegradable matrix is ​​matched with that of the porogen. After the porogen is completely degraded to form a through-porous structure, the matrix still maintains mechanical support. After the bone tissue is fully integrated, the matrix gradually degrades, achieving temporal synergy between mechanical support and bone regeneration. Attached Figure Description

[0037] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0038] Figure 1 Schematic diagram of the microstructure of porous bone cement matrix Figure reference numerals: 1-matrix; 2-porous structure; 3-biodegradable porogen; 4-microcapsule; 5-microsphere; 6-developer; 7-bioactivated modified layer. Detailed Implementation

[0039] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the protection scope of the present invention.

[0040] It should be understood that the orientation or positional relationship indicated in the terminology is based on the orientation or positional relationship shown in the accompanying drawings, and is only for the convenience of describing the present invention and simplifying the description, and is not intended to indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of the present invention.

[0041] Example 1

[0042] This embodiment provides a porous modified polymethyl methacrylate (PMMA) bone cement with bone-inducing function. The bone cement uses modified low-modulus PMMA bone cement as a matrix 1, in which a biodegradable porogen 3 and a contrast agent 6 are uniformly dispersed. The biodegradable porogen 3 consists of gelatin microcapsules 4 and gelatin microspheres 5, accounting for 8% of the mass of the biodegradable porogen 3 in the matrix 1. The particle size of the biodegradable porogen 3 is 200 μm, and the number of microcapsules 4 accounts for 10% of the number of microspheres 5, meaning that approximately 10 microspheres 5 are uniformly surrounding each microcapsule 4. The contrast agent 6 is barium sulfate, with a mass fraction of 2% added to the matrix 1. After in vivo degradation by the biodegradable porogen 3, the bone cement forms a porous structure 2 with a target porosity of 30%. The pore size in the cortical bone implantation area is 200 μm, and the pore size in the cancellous bone implantation area is 500 μm. The inner surface of the porous structure 2 is formed by a bioactivated modified layer 7 with a thickness of approximately 1 μm composed of the walls of the microcapsules 4. The biodegradable porogen 3 is prepared using highly cross-linked gelatin, with an in vivo degradation cycle of approximately 3 months, and the overall elastic modulus of the material is adjusted to approximately 0.5 GPa.

[0043] The wall of microcapsule 4 is loaded with anchoring factor GFOGER polypeptide and protective factors magnesium ions and zinc ions; in addition to the protective factor amifostine, the inner lumen of microcapsule 4 also contains migration factor SDF-1α (CXCL12); microsphere 5 is a solid structure containing migration factor PDGF-BB, repair factor recombinant bone morphogenetic protein-2 (BMP-2) and protective factor N-acetylcysteine.

[0044] The preparation method of this embodiment is as follows: First, gelatin microcapsules 4 are prepared using a double emulsion method (W / O / W). The particle size of microcapsules 4 is controlled to be 200 μm. The capsule walls are grafted with GFOGER peptides and loaded with magnesium and zinc ions. The inner cavity is encapsulated with SDF-1α and aminofistine. By controlling the degree of glutaraldehyde crosslinking, the in vivo degradation period of microcapsules 4 is approximately 3 months. Simultaneously, solid gelatin microspheres 5 are prepared using an emulsion crosslinking method. The particle size is 200 μm, and the interior is loaded with BMP-2, N-acetylcysteine, and PDGF-BB. The degree of crosslinking is consistent with that of microcapsules 4. Microcapsules 4 and microspheres 5 are thoroughly mixed at a ratio of 10:100, so that each microcapsule 4 is uniformly surrounded by approximately 10 microspheres 5. Subsequently, a mixture of biodegradable porogen 3 and barium sulfate is added to the modified low-modulus PMMA bone cement powder and dry-mixed evenly. The biodegradable porogen 3 accounts for 8% of the total mass, and barium sulfate accounts for 2% of the total mass. PMMA bone cement powder and liquid were mixed according to the solid-liquid ratio, injected into a mold, and cured at 37°C for 24 hours to obtain a porous bone cement solidified body. A bio-activated modified layer with a thickness of approximately 1 μm was naturally formed on the inner surface of the solidified body's pores through the microcapsule walls.

[0045] Example 2 This embodiment provides a porous calcium phosphate bone cement with bone-inducing function. The bone cement uses calcium phosphate cement (CPC) as a matrix 1, in which a biodegradable porogen 3 and a contrast agent 6 are uniformly dispersed. The biodegradable porogen 3 consists of chitosan microcapsules 4 and chitosan microspheres 5, accounting for 16.5% of the mass of the biodegradable porogen 3 in the matrix 1. The particle size of the biodegradable porogen 3 is 500 μm, and the number of microcapsules 4 accounts for 30% of the number of microspheres 5, meaning that approximately 3.3 microspheres 5 are uniformly surrounding each microcapsule 4. The contrast agent 6 is strontium-doped hydroxyapatite, added to the matrix 1 at a mass fraction of 7%. After in vivo degradation by the biodegradable porogen 3, the bone cement forms a porous structure 2 with a target porosity of 47.5%. The pore size in the cortical bone implantation area is 350 μm, and the pore size in the cancellous bone implantation area is 650 μm. The inner surface of the porous structure 2 is formed by a bio-activated modified layer 7 with a thickness of approximately 3 μm composed of the walls of the microcapsules 4. The biodegradable porogen 3 is prepared from medium-crosslinked chitosan, with an in vivo degradation cycle of approximately 13.5 months, and the overall elastic modulus of the material is adjusted to approximately 9.25 GPa.

[0046] The wall of microcapsule 4 is loaded with anchoring factor type I collagen P15 peptide and protective factors strontium ion and selenium ion; in addition to the protective factor cerium oxide nanozyme, the inner cavity of microcapsule 4 also contains migration factor E7 (SDF-1α mimic peptide); microsphere 5 is a solid structure containing migration factor SDF-1α, repair factor teriparatide PTH (1-34) and protective factor SOD mimic peptide.

[0047] The preparation method of this embodiment is as follows: First, chitosan microcapsules 4 are prepared by electrostatic spraying combined with ionic crosslinking. The microcapsule 4 has a particle size of 500 μm. The capsule wall is grafted with P15 peptide and loaded with strontium ions and selenium ions. The inner cavity is encapsulated with E7 peptide and cerium oxide nanozyme. By controlling the degree of crosslinking, the in vivo degradation cycle of microcapsule 4 is approximately 13.5 months. At the same time, solid chitosan microspheres 5 are prepared by extrusion-ionic crosslinking. The particle size is 500 μm. PTH (1-34), SOD-mimicking peptide and SDF-1α are loaded inside. Microcapsules 4 and microspheres 5 are thoroughly mixed at a ratio of 30:100, so that each microcapsule 4 is uniformly surrounded by about 3.3 microspheres 5. Then, the biodegradable pore-forming agent 3 mixture and strontium-doped hydroxyapatite are added to calcium phosphate bone cement powder and mixed evenly. The biodegradable pore-forming agent 3 accounts for 16.5% of the total mass, and the strontium-doped hydroxyapatite accounts for 7% of the total mass. Add curing liquid at a liquid-to-solid ratio of 0.4 mL / g, mix, and inject into a mold. Curing is carried out at 37℃ and 100% relative humidity for 72 hours to obtain porous calcium phosphate bone cement cured body. Microcapsule 4 forms a bio-activated modified layer of about 3 μm thick on the inner surface of the pores 7.

[0048] Example 3 This embodiment provides a porous magnesium phosphate bone cement with bone-inducing function. The bone cement uses magnesium phosphate bone cement as a matrix 1, in which a biodegradable porogen 3 and a contrast agent 6 are uniformly dispersed. The biodegradable porogen 3 consists of PLGA microcapsules 4 and PLGA microspheres 5, accounting for 25% of the mass of the matrix 1. The particle size of the biodegradable porogen 3 is 800 μm, and the number of microcapsules 4 accounts for 50% of the number of microspheres 5, meaning that approximately two microspheres 5 are uniformly surrounding each microcapsule 4. The contrast agent 6 is tantalum particles, with a mass fraction of 12% added to the matrix 1. After in vivo degradation by the biodegradable porogen 3, the bone cement forms a porous structure 2 with a target porosity of 65%. The pore size in the cortical bone implantation area is 500 μm, and the pore size in the cancellous bone implantation area is 800 μm. The inner surface of the porous structure 2 is formed by a bio-activated modified layer 7 with a thickness of approximately 5 μm composed of the walls of the microcapsules 4. The biodegradable porogen 3 was prepared using low-crosslinking PLGA, with an in vivo degradation cycle of approximately 24 months, and the overall elastic modulus of the material was adjusted to approximately 18 GPa.

[0049] The wall of microcapsule 4 is loaded with anchoring factor lentinin VN fragment and protective factors resveratrol and miR-34a; in addition to the protective factor amifostine, the lumen of microcapsule 4 also contains migration factor PDGF-BB; microsphere 5 is a solid structure containing migration factor E7 peptide, repair factor strontium ion (Sr²⁺) and protective factor cerium oxide nanozyme.

[0050] The preparation method of this embodiment is as follows: First, PLGA microcapsules 4 with a particle size of 800 μm were prepared using the double emulsion method. The capsule walls were grafted with VN fragments and loaded with resveratrol and miR-34a. The inner cavity was encapsulated with PDGF-BB and aminofistine. By controlling the molecular weight and cross-linking degree of PLGA, the in vivo degradation period of microcapsules 4 was made to be approximately 24 months. Simultaneously, PLGA solid microspheres 5 with a particle size of 800 μm were prepared using the emulsion solvent evaporation method. The microspheres were loaded with Sr²⁺, cerium oxide nanozyme, and E7 peptide. Microcapsules 4 and microspheres 5 were thoroughly mixed at a ratio of 50:100, so that each microcapsule 4 was uniformly surrounded by approximately two microspheres 5. Subsequently, a mixture of biodegradable porogen 3 and tantalum particles was added to magnesium phosphate bone cement powder and mixed evenly. The biodegradable porogen 3 accounted for 25% of the total mass, and the tantalum particles accounted for 12% of the total mass. After adding curing liquid according to the liquid-solid ratio and mixing, the mixture was injected into a mold and cured at 37°C for 48 hours to obtain a porous magnesium phosphate bone cement cured body. The microcapsule wall forms a bio-activated modified layer of about 5 μm thick on the inner surface of the pores.

[0051] Example 4 This embodiment provides a porous modified PMMA bone cement with bone-inducing function prepared using a foaming porogen. The bone cement uses modified low-modulus PMMA bone cement as a matrix 1, which contains a foaming porogen, a biodegradable porogen 3, and a contrast agent 6. The foaming porogen is a sodium bicarbonate-citric acid system, where sodium bicarbonate accounts for 3% of the mass of matrix 1, and citric acid accounts for 2.5% of the mass of matrix 1. During the curing stage of the bone cement paste, the two react chemically to release carbon dioxide gas, generating bubbles and forming a porous structure 2. The biodegradable porogen 3 consists of gelatin microcapsules 4 and gelatin microspheres 5, accounting for 12% of the mass of matrix 1. The particle size of the biodegradable porogen 3 is 400 μm, and the number of microcapsules 4 accounts for 20% of the number of microspheres 5, meaning that approximately 5 microspheres 5 are uniformly surrounding each microcapsule 4. The contrast agent 6 is barium sulfate, added to matrix 1 at a mass fraction of 5%. The bone cement forms a porous structure 2 through the synergistic effect of gas generation by a foaming porogen and degradation by a biodegradable porogen 3. The target porosity is 40%, with a pore size of 300 μm in the cortical bone implantation area and 600 μm in the cancellous bone implantation area. The inner surface of the porous structure 2 is composed of a bio-activated modified layer 7 with a thickness of approximately 2 μm formed by the walls of microcapsules 4. The biodegradable porogen 3 is prepared using medium-to-high cross-linked gelatin, with an in vivo degradation period of approximately 6 months, and the overall elastic modulus of the material is controlled to approximately 5 GPa.

[0052] Microcapsule 4 has an anchoring factor GFOGER peptide and a protective factor zinc ion loaded in its wall; in addition to the protective factor N-acetylcysteine, microcapsule 4 also contains the migration factor SDF-1α in its lumen; microsphere 5 is a solid structure containing the migration factor PDGF-BB, the repair factor BMP-2 and the protective factor SOD mimic peptide.

[0053] The preparation method of this embodiment is as follows: First, gelatin microcapsules 4 and microspheres 5 with a particle size of 400 μm are prepared according to the aforementioned method, and microcapsules 4 and microspheres 5 are mixed at a ratio of 20:100. Sodium bicarbonate, citric acid, biodegradable porogen 3 mixture and barium sulfate are added to the modified low modulus PMMA bone cement powder and mixed evenly by dry method. Bone cement monomer liquid is added according to the solid-liquid ratio for mixing. During the paste curing stage, sodium bicarbonate reacts with citric acid to release carbon dioxide gas, forming bubbles in the paste. At the same time, biodegradable porogen 3 is uniformly dispersed in the matrix 1. The mixed paste is injected into a mold and cured at 37°C for 24 hours to obtain a porous bone cement cured body. The pores formed by foaming are interconnected with the pores formed after the degradation of biodegradable porogen 3. The capsule wall of microcapsule 4 forms a bio-activated modified layer 7 with a thickness of about 2 μm on the inner surface of the pores.

[0054] Example 5 This embodiment provides a porous calcium sulfate bone cement using a combination of a foaming porogen and a biodegradable porogen 3. The bone cement uses calcium sulfate bone cement as a matrix 1, which contains the foaming porogen, the biodegradable porogen 3, and the developer 6. The foaming porogen uses a hydrogen peroxide system with a concentration of 3%, added at 8% of the curing liquid volume. During the curing stage of the paste, it decomposes to generate oxygen and form bubbles. The biodegradable porogen 3 consists of alginate microcapsules 4 and alginate microspheres 5, accounting for 20% of the mass of the matrix 1. The particle size of the biodegradable porogen 3 is 600 μm, with the number of microcapsules 4 accounting for 40% of the number of microspheres 5, meaning each microcapsule 4 is uniformly surrounded by approximately 2.5 microspheres 5. The developer 6 is strontium-doped hydroxyapatite, added at a mass fraction of 10% of the matrix 1. The bone cement forms a porous structure 2 through the synergistic effect of gas generation by a foaming porogen and degradation by a biodegradable porogen 3. The target porosity is 55%, with a pore size of 400 μm in the cortical bone implantation area and 700 μm in the cancellous bone implantation area. The inner surface of the porous structure 2 is composed of a bio-activated modified layer 7 with a thickness of approximately 4 μm formed by the walls of microcapsules 4. The biodegradable porogen 3 is prepared from alginate with a medium to low degree of cross-linking, and its in vivo degradation period is approximately 18 months. The overall elastic modulus of the material is controlled to approximately 12 GPa.

[0055] The wall of microcapsule 4 is loaded with anchoring factor type I collagen P15 peptide and protective factors strontium ion and selenium ion; in addition to the protective factor cerium oxide nanozyme, the inner cavity of microcapsule 4 also contains migration factor E7 peptide; microsphere 5 is a solid structure containing migration factor SDF-1α, repair factor teriparatide PTH (1-34) and protective factor resveratrol.

[0056] The preparation method of this embodiment is as follows: First, alginate microcapsules 4 and microspheres 5 with a particle size of 600 μm are prepared using the electrostatic droplet method, and corresponding active factors are loaded onto them respectively. Microcapsules 4 and microspheres 5 are mixed at a ratio of 40:100. The biodegradable pore-forming agent 3 mixture and strontium-doped hydroxyapatite are added to calcium sulfate bone cement powder and mixed evenly by dry method. Hydrogen peroxide is added to the curing liquid and mixed evenly, and then added to the powder according to the liquid-solid ratio. During the paste curing stage, hydrogen peroxide decomposes to generate oxygen and form bubbles. The mixed paste is injected into a mold and cured at 37°C for 24 h to obtain a porous calcium sulfate bone cement cured body. A bio-activated modified layer 7 with a thickness of about 4 μm is formed on the inner surface of the pores of microcapsule 4.

[0057] Comparative Example 1 This comparative example is basically the same as Example 2, except that the degradable porogen 3 has a particle size of 100 μm, and the resulting porous structure 2 has an average pore size of approximately 100 μm, with the cortical bone region having a pore size of approximately 80 μm and the cancellous bone region having a pore size of approximately 120 μm. The remaining formulation composition, active ingredient loading, and preparation method are consistent with Example 2.

[0058] Comparative Example 2 This comparative example is basically the same as Example 2, except that the degradable porogen 3 has a particle size of 1000 μm, and the resulting porous structure 2 has an average pore size of approximately 1000 μm, with the cortical bone region having a pore size of approximately 900 μm and the cancellous bone region having a pore size of approximately 1100 μm. The remaining formulation composition, active ingredient loading, and preparation method are consistent with Example 2.

[0059] Comparative Example 3 This comparative example is basically the same as Example 2, except that the biodegradable porogen 3 accounts for 5% of the mass of the matrix 1, and the resulting porous structure 2 has a porosity of about 18%. The remaining formulation composition, active factor loading and preparation method are the same as in Example 2.

[0060] Comparative Example 4 This comparative example is basically the same as Example 2, except that the biodegradable porogen 3 accounts for 30% of the mass of the matrix 1, and the resulting porous structure 2 has a porosity of about 75%. The remaining formulation composition, active factor loading and preparation method are the same as in Example 2.

[0061] Comparative Example 5 This comparative example is basically the same as Example 2, except that the thickness of the microcapsule 4 wall is controlled to 10 μm, and the bio-activated modified layer 7 partially blocks the pores after covering, reducing the effective pore size by about 40% compared to the design value. The remaining formulation composition, active factor loading and preparation method are the same as in Example 2.

[0062] Comparative Example 6 This comparative example is basically the same as Example 2, except that the walls, cavities, and microspheres 5 of microcapsules 4 are not loaded with any protective factors, but only contain anchoring factors, repair factors, and migration factors. The remaining formulation and preparation methods are consistent with Example 2.

[0063] Comparative Example 7 This comparative example is basically the same as Example 2, except that no developer 6 is added to substrate 1. The remaining formulation composition, active ingredient loading, and preparation method are the same as in Example 2.

[0064] Comparative Example 8 This comparative example uses commercially available medical PMMA bone cement, a traditional dense bone cement that does not contain pore-forming agents, has no porous structure,2 lacks a bio-activated modification layer7, and has no active ingredient loading, containing only approximately 10% by mass of barium sulfate as a contrast agent6. The elastic modulus of this bone cement is approximately 25 GPa, and its porosity is approximately 0%.

[0065] Comparative Example 9 This comparative example is basically the same as Example 4, except that the amount of the foaming pore-forming agent sodium bicarbonate-citric acid system is too large, with sodium bicarbonate accounting for 8% of the mass of matrix 1 and citric acid accounting for 7% of the mass of matrix 1, resulting in over-foaming. The resulting porous structure 2 has a porosity of about 80%, and some pore walls are broken to form ultra-large cavities. The remaining formulation composition, active ingredient loading, and preparation method are the same as in Example 4.

[0066] Comparative Example 10 This comparative example is basically the same as Example 2, except that: the porous structure 2 adopts a uniform pore size design, with the pore size of both the cortical bone region and the cancellous bone region being 500 μm, and there is no difference in pore size gradient. The remaining formulation composition, active factor loading, and preparation method are consistent with Example 2.

[0067] Mechanical property testing Examples 1, 2, and 3 were selected as representatives of the three groups of biodegradable porogens in this experiment. They correspond to the low, medium, and high boundary values ​​of the parameter range in the claims, respectively, with elastic moduli of 0.5 GPa, 9.25 GPa, and 18 GPa, respectively, which can fully cover the elastic modulus range of 0.5–18 GPa defined in the claims. Meanwhile, Examples 4 and 5 were selected as representatives of the foaming porogen group to verify the mechanical properties under the combined use of foaming porogen and biodegradable porogen. Comparative Example 1 (pore size 100 μm, below the lower limit) and Comparative Example 2 (pore size 1000 μm, above the upper limit) were selected to verify the effect of pore size exceeding the 200–800 μm range on mechanical properties; Comparative Example 3 (5% of biodegradable porogen 3, below the lower limit) and Comparative Example 4 (30% of biodegradable porogen 3, above the upper limit) were selected to verify the effect of porogen content exceeding the 8%–25% range on mechanical properties; Comparative Example 9 (over-foaming, porosity approximately 80%) was selected to verify the mechanical defects caused by improper foaming porogen dosage leading to porosity exceeding the upper limit; Comparative Example 10 (uniform pore size, no gradient structure) was selected to verify the mechanical adaptation advantage of gradient porous structure 2 compared to uniform pore size; Comparative Example 8 (commercially available dense PMMA bone cement) was selected as a prior art control.

[0068] Each selected sample was prepared into a φ6mm×12mm cylindrical standard specimen. Compression tests were conducted using a universal testing machine at a loading rate of 1mm / min. Stress-strain curves were recorded, and the elastic modulus and compressive strength were calculated. Six parallel samples were tested in each group, and the average value was taken. The test results are shown in the table below.

[0069] sample Elastic modulus (GPa) Compressive strength (MPa) Cortical bone compatibility Example 1 0.52 38.6 Matching cancellous bone Example 2 9.18 62.3 Matching cortical bone / cancellous bone Example 3 17.85 85.7 Matching upper limit of cortical bone Example 4 4.95 48.2 Matching cancellous bone / cortical bone Example 5 11.82 68.5 Matching cortical bone Comparative Example 1 14.2 58.9 High Comparative Example 2 2.1 22.5 Insufficient strength Comparative Example 3 16.8 71.2 High Comparative Example 4 1.8 18.3 Severely insufficient strength Comparative Example 8 25.3 95.6 Serious mismatch Comparative Example 9 1.2 12.6 Severely insufficient strength Comparative Example 10 10.2 60.1 Cortical bone area is higher / cancellous bone area is lower As shown in the table above, the elastic moduli of Examples 1 to 5 are all within the range of 0.5 to 18 GPa, which matches well with the mechanical parameters of human cancellous and cortical bone. Examples 4 and 5, using a combination of a foaming porogen and a biodegradable porogen 3, also achieved effective control of the elastic modulus. Comparative Examples 1 and 3, due to insufficient pore formation, have excessively high elastic moduli, posing a risk of stress shielding. Comparative Examples 2 and 4, due to excessively large pores, have significantly reduced compressive strength, failing to meet mechanical support requirements. Comparative Example 9, due to excessive foaming, has excessively high porosity and pore wall rupture, resulting in a compressive strength of only 12.6 MPa, which is severely insufficient. Comparative Example 10, due to the use of uniform pore size, has a high elastic modulus in the cortical bone region and a low elastic modulus in the cancellous bone region, failing to match both types of bone tissue simultaneously. Comparative Example 8, with its commercially available dense PMMA bone cement, has an elastic modulus far higher than that of human bone, exhibiting a significant stress shielding effect. This invention achieves precise matching of mechanical properties with the host bone by synergistically controlling pore size, porogen content, and foaming parameters within the scope defined in the claims.

[0070] Porosity and pore size distribution characterization In this experiment, Examples 1, 2, and 3 were selected as representatives of the three groups of biodegradable porogens, with target porosities of 30%, 47.5%, and 65%, respectively, corresponding to the lower limit, median, and upper limit of the 30%–65% porosity range defined in the claims. Meanwhile, Examples 4 and 5 were selected as representatives of the foaming porogen group to verify the porosity and pore size distribution characteristics under the foaming porogen method. Comparative Example 1 (pore size 100 μm, below the lower limit) was selected to verify the effect of excessively small pore size on pore connectivity and bone ingrowth space; Comparative Example 3 (5% biodegradable porogen 3, porosity approximately 18%, below the lower limit) was selected to verify the defect of insufficient porogen content leading to excessively low porosity; Comparative Example 4 (30% biodegradable porogen 3, porosity approximately 75%, above the upper limit) was selected to verify the situation where excessive porogen leads to excessively high porosity; Comparative Example 5 (modified layer thickness 10 μm, above the upper limit) was selected to verify the defect of excessively thick modified layer blocking pores and reducing effective pore size; Comparative Example 9 (over-foaming, porosity approximately 80%) was selected to verify the defect of excessive foaming porogen leading to porosity exceeding the upper limit and uneven pore size distribution; Comparative Example 8 (commercially available dense PMMA bone cement) was selected as a non-porous structure control.

[0071] The porosity, pore size distribution, and pore connectivity of each selected sample were characterized using mercury intrusion porosimetry and micro-CT with a resolution of 5 μm. Three parallel samples were tested in each group, and the average value was taken. The test results are shown in the table below.

[0072] sample Porosity (%) Average pore size (μm) Channel connectivity (%) Example 1 29.8 198 85 Example 2 47.2 495 92 Example 3 64.7 792 95 Example 4 39.6 385 88 Example 5 54.8 590 90 Comparative Example 1 28.5 98 62 Comparative Example 3 17.8 490 55 Comparative Example 4 74.6 510 96 Comparative Example 5 42.3 298 (Valid) 71 Comparative Example 8 0.2 — 0 Comparative Example 9 79.8 1250 (including extra-large cavity) 78 As shown in the table above, the porosity of Examples 1 to 5 was consistently within the range of 30% to 65%, the pore size was consistent with the design value, and the pore connectivity was greater than 85%, providing sufficient space for bone cell ingrowth. Examples 4 and 5 used a combination of foaming pore-forming agent and biodegradable pore-forming agent 3, with interconnected foaming and degradation pores, resulting in a good pore structure. Comparative Example 1 had too small a pore size and low connectivity, making it difficult for bone cells to ingrow; Comparative Example 3 had too low a porosity, resulting in insufficient space for bone ingrowth; Comparative Example 4 had too high a porosity, and although the connectivity was high, the mechanical strength was severely insufficient, as shown in Experiment 1; Comparative Example 5 had too thick a modified layer, which blocked the pores, reducing the effective pore size and decreasing the connectivity; Comparative Example 9 had an excessively high porosity of 79.8% due to over-foaming, resulting in overly large cavities, uneven pore size distribution, and damaged pore wall structure; Comparative Example 8 had a completely dense structure with no space for bone ingrowth. This invention achieves an optimal balance of porosity, pore size, and connectivity by synergistically controlling pore size, pore agent content, foaming parameters, and modified layer thickness within the scope defined in the claims.

[0073] Evaluation of cell compatibility and osteoinductive activity This experiment selected Examples 1, 2, and 3 as representatives of the three groups of biodegradable porogens, covering low, medium, and high parameters, which can comprehensively verify the osteoinductive activity of the material of the present invention under different parameter conditions; at the same time, Example 4 was selected as a representative of the foaming porogen group to verify cell compatibility and osteoinductive activity under the foaming porogen method. Comparative Example 1 (pore size 100 μm, below the lower limit) was selected to verify the defect of cells having difficulty entering the pores due to excessively small pore size; Comparative Example 2 (pore size 1000 μm, above the upper limit) was selected to verify the defect of cells not being able to effectively anchor due to excessively large pore size; Comparative Example 3 (degradable porogen 3 at 5%, porosity too low) was selected to verify the effect of insufficient bone ingrowth space on cell proliferation and osteogenic differentiation; Comparative Example 5 (modified layer 10 μm, above the upper limit) was selected to verify the negative impact of excessively thick modified layer blocking the pores on bone induction effect; Comparative Example 10 (uniform pore size, no gradient structure) was selected to verify the advantage of gradient porous structure 2 over uniform pore size in bone integration efficiency; Comparative Example 8 (commercially available dense PMMA bone cement) was selected as a non-bioactive control. Comparative Example 6 was not selected in this experiment because it only lacked the protective factor, and under conventional cell culture conditions without X-ray irradiation, its bone induction-related indicators were not significantly different from those of the examples. The role of the protective factor will be specifically verified in Experiment 6.

[0074] Bone marrow mesenchymal stem cells (3rd generation) were obtained from SD rats at a concentration of 1×10⁻⁶. 5Cells / mL were seeded onto the surface of selected samples and cultured at 37℃ and 5% CO2. After 4 hours of culture, DAPI staining was performed, and the number of adherent cells was counted under a fluorescence microscope. Cell proliferation activity was detected by CCK-8 assay after 1, 3, and 7 days of culture. Alkaline phosphatase (ALP) activity was detected after 7 and 14 days of culture. After 21 days of culture, Alizarin Red S staining was performed, and the mineralized nodule area was quantified. Each group had 3 replicates, and the experiment was repeated 3 times. The test results are shown in the table below.

[0075] As shown in the table above, the cell adhesion rate, proliferation activity, ALP activity, and mineralized nodule area of ​​Examples 1 to 4 were significantly higher than those of the comparative examples. Example 4, which used a combination of a foaming porogen and a biodegradable porogen 3, exhibited a multi-level pore structure that facilitated cell adhesion, proliferation, and osteogenic differentiation. In Comparative Example 1, the pore size was too small, making it difficult for cells to enter the pores; in Comparative Example 2, the pore size was too large, preventing effective cell anchoring; in Comparative Example 3, the low porosity limited cell growth space; in Comparative Example 5, the excessively thick modified layer blocked the pores, resulting in decreased osteoinduction; in Comparative Example 10, the use of a uniform pore size led to lower bone integration efficiency compared to the example with the gradient porous structure 2; and in Comparative Example 8, the lack of porous structure 2 and bioactivity resulted in cell growth only on the surface with almost no osteogenic differentiation. This invention significantly enhances osteoinduction activity through the synergistic effect of porous structure 2, bioactivated modified layer 7, and a multi-factor sustained-release system.

[0076] X-ray imaging performance test This experiment selected Examples 1, 2, and 3 as experimental groups, with the following amounts of developer 6 added: 2% (barium sulfate, lower limit), 7% (strontium-doped hydroxyapatite, median), and 12% (tantalum particles, upper limit), respectively. This comprehensively covers the 2%–12% developer 6 addition range defined in the claims and verifies the development effect of the three different developer 6. Comparative Example 7 (without developer 6) was selected as the core control to verify the necessity of developer 6 for X-ray detectability; Comparative Example 8 (commercially available PMMA bone cement, containing approximately 10% barium sulfate) was selected as a commercially available product control to compare the development performance differences between the present invention and conventional products.

[0077] Each selected sample was placed in a simulated tissue equivalent material and radiographed using a clinical X-ray machine. The clarity of the imaging was assessed using a blind method, with a 5-point scoring system, where 5 points represents very clear and 1 point represents invisible. The test results are shown in the table below.

[0078] sample Rendering clarity rating Distinguishing bone healing interface Example 1 3.8 Distinguishable Example 2 4.5 Clearly distinguishable Example 3 5.0 Very clear Comparative Example 7 1.2 Indistinguishable Comparative Example 8 4.2 Distinguishable As shown in the table above, in Examples 1 to 3, the amount of contrast agent 6 added ranged from 2% to 12%, and all samples were clearly visible under X-rays. Comparative Example 7, lacking contrast agent 6, was almost invisible under X-rays, making it impossible to monitor bone healing. The present invention has a reasonable range for the amount of contrast agent 6 added, balancing both imaging effectiveness and material mechanical properties.

[0079] Evaluation of X-ray radiation protection and remediation effects This experiment selected Examples 1, 2, and 3 as experimental groups, all of which contained protective factors, to verify the radiation protection effect of the present invention under different parameter conditions. Comparative Example 6 (without any protective factor) was selected as the core control. Except for the absence of protective factors, the formulation of this comparative example was completely identical to Example 2, directly demonstrating the crucial role of protective factors in radiation protection. Comparative Example 8 (commercially available dense PMMA bone cement, without protective factors) was selected as a prior art control to demonstrate the deficiency of traditional products in providing no protection to bone cells under X-ray irradiation. A blank control group (no irradiation) and an irradiation-only group were also set up as baseline controls. Other comparative examples were not selected in this experiment because the parameter differences in other comparative examples (such as pore size, pore-forming agent content, etc.) do not directly affect the radiation protection effect. Selecting Comparative Example 6 allows for single-variable control, making the experimental conclusions more convincing.

[0080] Bone marrow mesenchymal stem cells were seeded into the extracts of selected samples and cultured for 24 hours before being irradiated with X-rays at a dose of 4 Gy and a dose rate of 1 Gy / min. 24 hours post-irradiation, cell viability was assessed using the CCK-8 assay, intracellular reactive oxygen species (ROS) levels were detected using the DCFH-DA probe, and DNA damage was assessed using a comet assay (expressed as olive tail moments). Cells were cultured for another 7 days after irradiation, and the colony formation rate was then measured. The results are shown in the table below.

[0081] sample Cell viability (%) ROS level (relative fluorescence intensity) DNA damage (Olive tail moment) 7-day clone formation rate (%) Blank control 100 1.00 3.2 85.6 Simple irradiation group 42.5 4.85 38.6 12.3 Example 1 78.2 1.85 12.5 52.8 Example 2 85.6 1.42 8.6 68.5 Example 3 82.3 1.58 10.2 62.3 Comparative Example 6 45.8 4.62 35.8 15.6 Comparative Example 8 41.2 4.95 40.2 10.8 As shown in the table above, after X-ray irradiation, the cell survival rate in Examples 1 to 3 was significantly higher than that in the simple irradiation group and Comparative Example 6. ROS levels and DNA damage were significantly reduced, and colony formation rate recovered significantly after 7 days. Comparative Example 6, lacking protective factors, showed no significant difference in cell survival rate, ROS levels, and DNA damage compared to the simple irradiation group, thus offering no radiation protection. Comparative Example 8, commercially available PMMA bone cement, also showed no radiation protection effect. This invention, through the sustained release of protective factors (magnesium ions, selenium ions, strontium ions, zinc ions, cerium oxide nanozyme, amifostine, N-acetylcysteine, SOD-mimicking peptide, resveratrol, miR-34a), effectively reduces X-ray damage to bone cells and promotes post-injury repair, resolving the contradiction between bone healing monitoring and radiation damage.

[0082] The above experimental results show that, by controlling the pore size to 200 to 800 μm, the mass percentage of the biodegradable porogen 3 to 8% to 25%, the porosity to 30% to 65%, the thickness of the bio-activated modified layer 7 to 1 to 5 μm, the mass fraction of the developer 6 to 2% to 12%, and the ratio of the number of microcapsules 4 to the number of microspheres 5 to 10% to 50%, and by rationally combining the foaming porogen and the biodegradable porogen 3, the following beneficial effects are achieved in the embodiments of the present invention: (1) The elastic modulus of the material is precisely matched with the mechanical parameters of human cancellous and cortical bone, thus fundamentally eliminating stress-shielding osteoporosis. (2) Through the synergistic effect of porous structure 2, bio-activated modified layer 7 and microcapsule 4 and microsphere 5 sustained-release system, bone cell anchoring, migration, proliferation and osteogenic differentiation are significantly promoted, realizing the bio-bone integration of bone cement and host bone; (3) Contrast agent 6 enables the bone healing process to be clearly monitored by X-rays, while the sustained release of protective factors effectively reduces and repairs bone cell damage caused by X-rays, thus resolving the contradiction between bone healing monitoring and radiation damage. (4) The foaming pore-forming agent generates gas during the curing stage to form primary pores, and the degradable pore-forming agent 3 degrades to form secondary pores. The two are used together to construct a multi-level interconnected porous structure 2, which further improves the bone ingrowth efficiency.

[0083] Each comparative example exhibited varying degrees of performance degradation due to parameters exceeding the scope defined in the claims of this invention: excessively small pore sizes hindered osteoblast ingrowth; excessively large pore sizes resulted in weak interfacial bonding and insufficient mechanical strength; insufficient content of biodegradable porogen 3 led to inadequate porosity; excessive content of biodegradable porogen 3 caused premature loss of mechanical strength; excessive foaming porogen resulted in excessive porosity and pore wall rupture; excessively thick modified layers caused pore blockage; the absence of protective factors resulted in no radiation protection; the absence of contrast agent 6 made it impossible to monitor bone healing; and traditional dense bone cement resulted in stress shielding and lack of bone integration. This demonstrates that the parameter range defined in the claims of this invention is a necessary condition for achieving the aforementioned beneficial effects.

Claims

1. A porous bone fixation material with bone-inducing function, characterized in that, The porous bone fixation material comprises a matrix, a porogen, and a contrast agent; the matrix includes a biodegradable matrix and a non-biodegradable matrix; the matrix is ​​selected from modified low-modulus polymethyl methacrylate bone cement, calcium phosphate bone cement, magnesium phosphate bone cement, and calcium sulfate bone cement; the matrix contains anchoring factors, repair factors, and protective factors; the anchoring factors are one or more of GFOGER peptide, type I collagen P15 peptide, and vitrin VN fragment; the repair factors are one or more of recombinant bone morphogenetic protein-2, teriparatide PTH, and strontium ions; the protective factors are one or more of magnesium ions, selenium ions, strontium ions, zinc ions, cerium oxide nanozyme, amifostine, N-acetylcysteine, SOD mimic peptide, resveratrol, and miR-34a; the biodegradable porogen is distributed in the matrix, and the mass of the biodegradable porogen in the matrix accounts for... The ratio is 8%-25%; the biodegradable porogen includes microspheres and microcapsules, the biodegradable porogen material is one or more of pharmaceutical gelatin, chitosan, PLGA, and alginate, the porogen particle size is 200-800 μm, and the in vivo degradation cycle of the biodegradable porogen is 3-24 months; the number of microcapsules in the biodegradable porogen accounts for 10%-50% of the number of microspheres; the outer layer of the microcapsule is the capsule wall, the capsule wall contains the anchoring factor and protective factor, and the inner cavity of the microcapsule contains the protective factor and migration factor; the microsphere is a solid, and the microsphere contains the repair factor, protective factor and migration factor; the migration factor is one or more of SDF-1α, E7 peptide and PDGF-BB; the amino acid sequence of the E7 peptide is EPLQLKM; the inner surface of the porous structure is provided with a bio-activated modified layer; the developer is uniformly dispersed in the matrix.

2. The porous bone fixation material according to claim 1, characterized in that, The porous structure has a pore size of 200-800μm, which reduces the stress of the porous bone fixation material and adjusts the elastic modulus to 0.5-18GPa.

3. The porous bone fixation material according to claim 1, characterized in that, The porous bone fixation material adapts to the mechanical properties of bone tissue through a pore size gradient. The cancellous bone implantation area adopts a large pore size structure of 500-800μm, and the cortical bone implantation area adopts a small pore size structure of 200-500μm.

4. The porous bone fixation material according to claim 1, characterized in that, The porous bone fixation material also includes a foaming porogen, which is distributed in the matrix and releases carbon dioxide or oxygen through a chemical reaction, generating bubbles during the curing stage of the paste. The foaming porogen system is one of the following: sodium bicarbonate-citric acid system, ammonium bicarbonate system, ammonium carbonate system, and hydrogen peroxide system.

5. The porous bone fixation material according to claim 1, characterized in that, The biodegradable porogen is matched with a corresponding doping ratio according to the required porosity and bone regeneration rate, so that the porosity of the porous structure is kept stable at 30%-65%.

6. The porous bone fixation material according to claim 1, characterized in that, The bio-activated modified layer has a thickness of 1-5 μm and uniformly covers the inner surface of the porous structure.

7. The porous bone fixation material according to claim 1, characterized in that, The components of the contrast agent are selected from one or more of barium sulfate, strontium-doped hydroxyapatite, and tantalum particles, and account for 2%-12% of the total mass of the porous bone fixation material.

Citation Information

Patent Citations

  • Gradient pore-forming magnesium-containing calcium phosphate bone repair material and preparation method thereof

    CN120437377A

  • Drug-loaded microsphere modified porous calcium phosphate bone cement as well as preparation method and repair material thereof

    CN122272894A